National Identity in Contemporary Conditions of Transformation of Value System - Demirchyan, Movses (Bulletin of Yerevan University E: Philosophy, Psychology, 2013)
The paper analyzes the process of globalization in terms of the impact on the system of self-identification, in particular, on the transformation of national identity. It is known that it is in danger of extinction due to the leveling and aggressive distribution in traditional societies’ global (uniform) system of consumer values. For national identity in this context, there is only one way to survive - the transformation of nation from traditional to political. The process of modernization is also indicated by the fact that the core of this modernization is the modernization of the nation’s moral, which involves the construction of a new hierarchy of values. It is highlighted that such modernization can take place only under the influence of a targeted system of self-identifications on the society (nation), resulting in possible formation of a political nation – a new community of people for whom the ethnic, religious, and cultural differences in the future are less important than the resolution of common social problems. However, as a rule, this process of formation of a new identity is initiated by the political power that comes to the realization of the need to build a system of social relations based on new principles and relevant objectives, but, as the experience of postSoviet countries shows, this need may go unnoticed. As a result, the society begins to form not transpersonal values (to what are the concerns and values of the political nation), but more personal, consumer, which are characterized as bourgeois. They are a direct threat to national identity, as depriving the system of self-identification of such unites transpersonal orientation as the experience of the past, traditions, culture and history, national and state interests and goals are. The threat to national identity in the system of bourgeois values exist on the ontological level, because the spread of bourgeois values (as opposed to national) facilitated by the fact that in a consumer society more viable are exactly the bourgeois values that contribute to a more well-being.